The Effect of Self-Awareness on Students’ Career Choice: Pengaruh Self-Awareness terhadap Pemilihan Karir Siswa - Intan, Nur; Puswiartika, Dhevy; Rasido, Ikhlas; Riyadi, Nur Eka Wahyuningsih (Jurnal Inovasi, Evaluasi dan Pengembangan Pembelajaran, 2025)
This study aims to analyze the influence of self-awareness on students’ career choices at SMA Negeri 5 Palu. Self-awareness is understood as an individual’s ability to recognize personal potential, emotions, and values, which plays a crucial role in career decision-making. A quantitative approach with a survey method was employed, and the sample consisted of 152 twelfth-grade students selected through proportional sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression. The findings reveal a positive and significant influence of self-awareness on students’ career choices, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.383. These results indicate that the higher the level of students’ self-awareness, the more accurate their career decision-making tends to be. Therefore, enhancing self-awareness through career guidance programs in schools is strongly recommended as a strategic effort to support students in their career planning